Knowledge regarding Zika Virus Infection among Healthcare Providers in an Academic Tertiary Care Center in Riyadh, Saudi Arabia: A Cross-Sectional Survey Study. (11th March 2020) - Alessa, Mohammed; Alzahrani, Mohammed; Alshehri, Abdulmajeed; Aljrboa, Amjad; Bustami, Rami; Almangour, Abdullah; Alsalem, Abdulaziz; Gramish, Jawaher; Khobrani, Moteb; Almangour, Thamer A.
Abstract : Background . Zika virus (ZIKV) has become a major concern across the world. It is highly necessary for healthcare providers (HCPs) to have sufficient knowledge about such a disease. The purpose of this study is to assess the knowledge regarding ZIKV among HCPs in Riyadh, Saudi Arabia. Materials and Methods . A cross-sectional survey study was conducted at a tertiary care center in Riyadh, KSA, during a two-month period from September 19, 2016 to November 19, 2016. Descriptive statistics were performed on data collected. For continuous variables, data were expressed as means ± standard deviations (SDs), medians, and ranges. Proportions were used to describe categorical variables. Knowledge scores were evaluated and compared by demographic characteristics including age, designation, years of practice, and gender, using the t -test/Mann–Whitney U test or the Kruskal–Wallis test, as appropriate. Results . A total of 336 HCPs from different specialties (physicians, dentists, nurses, pharmacists, and nutritionists) completed the questionnaire. Significant differences in knowledge about ZIKV were observed by participant's age. Significantly higher knowledge levels were observed among older participants (45 years or more; p = 0.011 ). A substantial difference in the knowledge level was observed by department, with pairwise comparisons showing significant differences in knowledge scores between all departments except for Pharmacy vs. Nutrition and Nursing vs. Internal Medicine. Knowledge scores were not significantly different by years of practice. Conclusion . Our study showed inadequate knowledge of HCPs from different specialties about ZIKV infection which needs to be improved in terms of infection prevention and control. Awareness about ZIKV infection should be ensured and maintained among HCPs to face any possible emergence in the region.